A vidék és a vidéki térségek meghatározásának európai vonatkozásai: történeti áttekintés az Európai Bizottság új város-vidék tipológiája apropóján - Kis, Krisztián (Jelenkori Társadalmi és Gazdasági Folyamatok, 2011)
The paper reviews the European attempts to designate rural areas, major institutional definitions and the existing practice. The presented rural designations are mostly recommendations, serving statistical purposes, but in neither case constitute as designation for development. Designations for this purpose are under national competence, during which the characteristics of settlement structures, population density, land use and certain socio-economic indicators are taken into account. Whatever approach we take in designating rural areas or defining rural, we need to have relevant information capturing characteristics of rural areas, as well as such geographic units which help to perform rural designation. To this end the European Commission recently introduced a new method, which allows designating urban and rural areas more precisely.